The wind from vulture peak : the buddhification of Japanese Waka in the Heian period - Miller, Stephen D., 1949- (Cornell East Asia series ;, 2013)
The Wind from Vulture Peak addresses the history of the gradual incorporation of Buddhist concepts into Heian waka poetry and the development among court poets of a belief in the production of that poetry as a Buddhist practice in itself.